Cooling history (from magma ascent to lava extrusion) of the Watuadeg pillow lava, Berbah, Yogyakarta, Indonesia - Indranova Suhendro; Agung Harijoko; Nugroho Imam Setiawan; Haryo Edi Wibowo (Journal of Applied Geology, 2023)
The Watuadeg pillow lava (WPL) is known as one of the most famous pillow lava outcrops in Yogyakarta, Indonesia, and its origin has been attributed to rapid-cooling process of subaqueous lava extrusion. However, there is no quantitative evidence that implies such hypotheses. Therefore, this study aims to reduce such a gap by revealing the cooling times (t) of WPL on the basis of a quantitative approach. In particular, we measured the size distribution (CSD) and number density (MND) of plagioclase microlites from the core, medial, and marginal (rim) domains of WPL. We found that the CSD slope significantly increases towards marginal zones, namely 30.4ᵒ for the core, 53.4ᵒ for the medial, and 228.1ᵒ for the rim. Because CSD slope is inversely proportional to cooling time ( ), by assuming a typical plagioclase microlite growth rate (G) of 1×107 mm/s, it is therefore inferred that the rim experienced the fastest cooling time (±12.1 hours), followed by the medial and core ((±52.0 and 91.4 hours, respectively). The fact that MNDs value increases toward the marginal zones also does not deny this idea (0.3×1016 m-3 for the core, 1.4×1016 m-3 for the medial, and 2.4×1016 m-3 for the rim), as higher MND with the domination of acicular-spherulitic habit represents a higher degree of undercooling. Because microlite is syn-eruptive product, our estimation represents the cooling time of magma since it migrated from the reservoir to the surface.